Marketing Communication Adaptation In Music Industry In Indonesia Amidst The Covid19 Pandemic: A Case Study Of Independent Musicians - Gus Abdurrahman Wahid, Alvin (KOMUNIKA, 2021)
The entertainment industry is one of the most affected industries by the COVID-19 pandemic. Not only in the international music industry, the Indonesian music industry is also experiencing similar issues, for example, workers in the indie music industry in Jakarta and its surroundings cannot run from the impacts of the pandemic. With the implementation of social distancing, physical distancing, as well as PSBB implemented by the government, creative industry, especially in the music sub-sector, must be able to adapt in creating new works that are marketed digitally. However, this kind of online activities have made plenty of changes in music culture. In this study, the author explores for literature of the last 5 years or those that are still relevant to this research with the theme of how the music industry in Indonesia has adapted during the COVID19 pandemic. The author uses interview method in this study. interviews are conducted with musicians and other music industry players (small bands/small musicians) within the independent music scene. In conclusion, independent musicians should try harder in marketing their music and communicating with fans, interactions that generate engagement on their social media pages are the key so that fans can still remember the musicians and their works.